Addressing the Financial Burden of Diabetes Patients in India: Future Health Strategies - Paswan , Pappu Kumar (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
In India diabetic people are estimated to come to near about 8 crores by 2030.The total yearly economic burden by diabetics on their treatment was, on average, 10,000 INR in urban areas and 6260 INR in rural areas. A survey in India during the years 2008 and 2009 found that total costs for patients without complications were 4493 INR compared to14,692 INR for patients with severe complications. The present review article highlights diabetes treatment ruins the ruler as well as urban people of India. The Government of India implemented Rashtriya Swasthya Bima Yojana (RSBY) a health insurance scheme, under this facility BPL families get protected from health expenses up to 30,000 INR expending load in the rural as well as urban inhabitants of India.